2005
DOI: 10.1039/b415908j
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]arene-cholic acid conjugates: a new class of efficient synthetic ionophores

Abstract: The synthesis of a new class of amphiphilic calix[4]arene-based ionophores, relying on direct reductive amination as a key step, and the evaluation of their H+ and Na+ transporting properties is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Calixarene scaffold has also been used as a central relay for the construction of tunnel or pore-like ion channels. In these calix [4]arene hybrid derivatives 55-58, central calix [4]arene unit was appended with either dodecyl chains terminated with 10-benzyl-1,10-diaza [18]crown-6 units, cholic acid, or oligoether derivatives in an 1,3-alternate conformation, respectively (Chart 5) [5,[82][83][84][85][86]. The length of these molecules would be sufficient to completely span the thick lipid bilayer and transport Na + ions selectively through unimolecular channel pathway across the lipid bilayer.…”
Section: Ion Channels Developed From Tunnel or Pore Type Of Cylindricmentioning
confidence: 99%
“…Calixarene scaffold has also been used as a central relay for the construction of tunnel or pore-like ion channels. In these calix [4]arene hybrid derivatives 55-58, central calix [4]arene unit was appended with either dodecyl chains terminated with 10-benzyl-1,10-diaza [18]crown-6 units, cholic acid, or oligoether derivatives in an 1,3-alternate conformation, respectively (Chart 5) [5,[82][83][84][85][86]. The length of these molecules would be sufficient to completely span the thick lipid bilayer and transport Na + ions selectively through unimolecular channel pathway across the lipid bilayer.…”
Section: Ion Channels Developed From Tunnel or Pore Type Of Cylindricmentioning
confidence: 99%
“…Interestingly, the ability of these compounds to act as a monomeric or self-assembled pore depended on the flexibility of the steroid linker [20]. An ionophore designed by Izzo, De Riccardis, and colleagues appends cholic acid units to a calix [4]arene scaffold [21]. Various derivatives of two fixed calix conformations, 1,3alternate, 14, and cone, 15, were observed to accelerate the rates of H + and Na + transport in a dose dependent manner.…”
Section: Monomeric Channelsmentioning
confidence: 99%
“…Jin et al have shown that the cone conformation of the tetra-ester derivative (XI & XII) of the calix [4]arene is highly selective for Na + ions (Figure 32) and that there is a possibility that the calixarene forms a dimer in the membrane to function either as a channel or as a shuttle 72 . The 1,3-alternate calixarenes are much more efficient than the cone calixarenes and this has led to the idea that they may function by a different transport procedure 73 . Maulucci et al carried out work on the calix [4]arenes derivatives (XIII a-e) shown in Figure 33 and have reasoned that the 1,3-alternate forms are large enough to span the bilayer but that the cone forms need to dimerise 73 .…”
Section: Applications Of Calixarenesmentioning
confidence: 99%
“…The 1,3-alternate calixarenes are much more efficient than the cone calixarenes and this has led to the idea that they may function by a different transport procedure 73 . Maulucci et al carried out work on the calix [4]arenes derivatives (XIII a-e) shown in Figure 33 and have reasoned that the 1,3-alternate forms are large enough to span the bilayer but that the cone forms need to dimerise 73 . Without this need to dimerise, it is possible that the 1,3-alternate is able to form a more efficient channel.…”
Section: Applications Of Calixarenesmentioning
confidence: 99%
See 1 more Smart Citation